2006
DOI: 10.1111/j.1574-6968.2006.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Truffles: much more than a prized and local fungal delicacy

Abstract: Truffles are hypogeous fungi which live in symbiosis with plant host roots in order to accomplish their life cycle. Some species, such as Tuber magnatum Pico, the 'white truffle', and Tuber melanosporum Vittad., the 'black truffle', are highly appreciated in many countries because of their special taste and smell. The great demand for the black and white truffles, the increasing attention towards other species of local interest for the rural economy (such as T. aestivum) together with a drop in productivity, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
166
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 201 publications
(171 citation statements)
references
References 48 publications
2
166
0
3
Order By: Relevance
“…Tuber melanosporum grows in symbiosis with several oak species and hazelnut trees in France, Italy, and the Iberian Peninsula, and has also been introduced successfully, from these Mediterranean areas, to New Zealand, Australia, Israel, and North America ( Mello et al 2006). Previous work on the composition of fungal communities inside and outside of the T. melanosporum brûlés revealed clear differences between the fungal communities, as well as a lower fungal biodiversity inside the brûlé ( Napoli et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tuber melanosporum grows in symbiosis with several oak species and hazelnut trees in France, Italy, and the Iberian Peninsula, and has also been introduced successfully, from these Mediterranean areas, to New Zealand, Australia, Israel, and North America ( Mello et al 2006). Previous work on the composition of fungal communities inside and outside of the T. melanosporum brûlés revealed clear differences between the fungal communities, as well as a lower fungal biodiversity inside the brûlé ( Napoli et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mycologists have described around 200 European species, varieties and forms of Tuber over the centuries (Ceruti et al, 2003); however, only the development of molecular tools has allowed construction of reliable phylogenetic trees (Jeandroz et al, 2008) and validation of around 32 species in Europe (Ceruti et al, 2003). Meanwhile, speciesspecific probes have allowed truffle species to be identified at different phases of their life cycle (Mello et al, 2006), and the same technology can identify truffle fraudsters . Moreover, it has been possible to widen the range of known truffle hosts: they are traditionally associated with trees and shrubs, but have now also been located inside orchid roots (Selosse et al, 2004), suggesting that truffles possess a more flexible host range.…”
Section: Introductionmentioning
confidence: 99%
“…are in particular appreciated in the market because of their organoleptic and flavor properties, both as fresh fruiting bodies and as ingredients in processed products (oil, cheese, pasta, sauce, etc.). Of all the truffle species, the white truffle Tuber magnatum and the black truffle Tuber melanosporum are the most precious, with a request that is much higher than the offer in the food market (Mello et al 2006). It has already been reported that post-harvest storage can have an impact on mushroom quality (Sakamoto et al 2009;Eastwood et al 2011).…”
Section: Introductionmentioning
confidence: 99%